ATTITUDES ABOUT VULVA HYGIENE AND THE INCIDENCE OF VAGINAL DISCHARGE AT SMA NEGERI 13 SURABAYA - Selly Sukmawati (Global Ten Public Health and Nursing Journal, 2025)
AbstractIntroduction: Vaginal discharge is a problem of female reproductive organs that often occurs in adolescents in Indonesia. This study aims to determine the relationship between knowledge and attitudes of adolescent girls about vulva hygiene and the incidence of vaginal discharge at SMA Negeri 13 Surabaya. Methods: This study used a type of correlational analytical research with a cross-sectional approach. A sample of 65 young women was taken using the proportionete Stratified Random Sampling technique. The independent variable is the knowledge and attitude of adolescent girls, the dependent variable is the incidence of vaginal discharge. The data were analyzed with univariate, bivariate using Chi Square with a value of α = 0.05. Results and Data Analysis: The results of this study showed that out of 65 adolescent girls, most of the adolescent girls (52.3%) had good knowledge, most of the adolescent girls (70.8%) had a positive attitude, most of the adolescent girls (66.2%) experienced physiological vaginal discharge. Most adolescent girls (69.8%) are well-informed to experience physiological vaginal discharge. The results of the Chi Square test were obtained that there was a relationship between adolescent girls' knowledge of vulva hygiene and the incidence of vaginal discharge (p-value = 0.001 < α = 0.05). Almost all adolescent girls (88.4%) have a positive attitude of experiencing physiological vaginal discharge. The results of the Chi Square test obtained that there was a relationship between adolescent girls' attitudes about vulvar hygiene and the incidence of vaginal discharge (p-value = 0.001 < α = 0.05). Conclusion: Adolescent girls' knowledge of vulvar hygiene is mostly in the good category. Adolescent girls' attitudes about vulvar hygiene are mostly positive. There is a relationship between knowledge and the occurrence of vaginal discharge. There is a relationship between attitude and the incidence of vaginal discharge. Advice for young women to do vulva hygiene properly and correctly to prevent vaginal discharge. For schools, it is hoped that they can add books in the library related to the hygiene of the reproductive organs of adolescent girls as educational materials and can carry out counseling on the hygiene of female reproductive organs.Keywords: Knowledge, Attitude, Vulva Hygiene, Vaginal Discharge